2011
DOI: 10.1016/j.juro.2010.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Sprayed Fibrin Sealant as the Sole Hemostatic Agent for Porcine Laparoscopic Partial Nephrectomy

Abstract: Sprayed Tisseel without suturing effectively sealed the arterial and collecting system after severe laparoscopic partial nephrectomy in the porcine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The knee was closed in layers prior to performing a carbon dioxide (CO 2 ) insufflated arthroscopy (Smith & Nephew) with a standard anterolateral approach. The two-component holder of the cell laden (2 Â 10 6 cells/ml) fibrin glue was connected to the DuploSpray system which was originally designed to spray a fibrin sealant as a hemostatic agent for laparoscopic surgery 17,18 . For the cadaveric study, both chondrons (n ¼ 3) and chondrocytes (n ¼ 5) were used.…”
Section: Cadaveric Studymentioning
confidence: 99%
“…The knee was closed in layers prior to performing a carbon dioxide (CO 2 ) insufflated arthroscopy (Smith & Nephew) with a standard anterolateral approach. The two-component holder of the cell laden (2 Â 10 6 cells/ml) fibrin glue was connected to the DuploSpray system which was originally designed to spray a fibrin sealant as a hemostatic agent for laparoscopic surgery 17,18 . For the cadaveric study, both chondrons (n ¼ 3) and chondrocytes (n ¼ 5) were used.…”
Section: Cadaveric Studymentioning
confidence: 99%
“…Margulis et al confirmed the effect of a new inorganic hemostatic agent on the model of open and laparoscopic partial nephrectomy in pigs without the use of supportive hemostatic techniques 18. Similarly, Pick et al19 confirmed the effect of sprayed fibrin sealant.…”
Section: Discussionmentioning
confidence: 92%
“…Tisseel glue can withstand an arterial pressure of up to 350 mmHg before it is dislodged from renal parenchyma. 11 Patients undergoing OPNs are placed in flank position, and a supra 12th rib incision is made. The kidneys are dissected in the retroperitoneal space and the renal lesion(s) identified.…”
Section: Methodsmentioning
confidence: 99%